Tiempo y temperatura del escalado para la obtención de la pulpa de camote (ipomea batata) y elaboración de mermelada - Suarez Arana, Kerly Mariana (2015)
This research took place at the Experimental Farm "La Maria" State Technical University of Quevedo (UTEQ), in the Laboratory of Food Science, Faculty of Animal Science, and Located at Km 7 1/2 via Quevedo - El Empalme in the Province of Rivers. The objectives of this study were: Determine the time and temperature of blanching in the pulping sweet potato (IpomeaBatata) and jam-making. Was applied2 factorial arrangement (times) and 2 (temperature) applying a completely randomized design (CRD) with five repetitions and for comparison in between the Tukey test (p ≤ 0.05)% was used was applied. In the organoleptic variables such as taste, odor, color and acceptability krukallwallis test was applied (p ≤ 0.05)%. The variables Brix and acidity if there were statistical differences between treatments issuing values (10.98 and 11.38) to (17.95 and 24.16%) ° brix respectively (0.06 and 0.1%) acidity while for pH there were no statistical differences but differences with numerical values (5.86 and 6.03) in pH. With regard to organoleptic analysis presented marmalade; more taste, color and flavor with sucrose, and greater acceptability with honey. Regarding the benefit / cost of 2.43 indicating that the T1 (sucrose) treatment and 1.01 for treatment T2 (honey), indicating that the best treatment is the T1 which posted a return of 143% while the T2 posted a return of 1.34.